Titanium alloys surface integrity of belt grinding considering different machining trajectory direction - Jiang, Guiyun; Yang, Hang; Xiao, Guijian; Zhao, Zeyong; Wu, Yuan (Frontiers in Materials, 2022)
The interplay of abrasive grains and materials complicates the grinding of titanium alloys by abrasive belts. For example, the influence relationship of surface generation for complex curved workpieces such as hollow blades needs to be clarified, making precise control of the surface integrity of complex surfaces difficult in abrasive belt grinding applications. This paper thus proposes a path planning method based on the direction of interactive motion of grinding grains and materials to reveal its influence law on the surface integrity of complex curved titanium alloy surfaces with uneven distribution of machining allowances. First, a path planning method with different angles of grinding direction and feed direction is proposed. In order to determine the corresponding experimental scheme for hollow titanium alloy blades. Experimental results are used to analyze the influence of different path planning directions on the surface roughness, residual stress, surface topography, and accuracy of the contours. The results were tested for reliability.